ПОМЕЃУ КАЗНАТА ЗАТВОР И УСЛОВНАТА ОСУДА: ПРЕДНОСТИ И НЕГАТИВНИ СТРАНИ ОД (НЕ)ПРИМЕНАТА НА АЛТЕРНАТИВНИТЕ МЕРКИ И НА КАЗНАТА ЗАТВОР - Gruevska Drakulevski, Aleksandra (MACEDONIAN JOURNAL FOR CRIMINAL LAW AND CRIMINOLOGY, 2017)
The author of the paper deals with the basic problem of the criminal law theory and practice - identification, choice of means and methods, sanctions for the most successful, most efficient prevention, suppression and prevention of crime. Analyzing the penal policy of the courts in the country, the author concludes that sanctions that are mostly imposed by the courts are imprisonment and conditional prison sentence. Imprisonment is used too much; and conditional prison sentence is used even more. And between the two penalties there is almost a vacuum of imposing other sanctions. This is a trend that we see not only in the domestic case law, but also in many other countries. Further in the paper the author sets out the main criticisms to imprisonment and the advantages of the alternative measures. Opposing the arguments regarding the advantages and disadvantages of (non)application of alternative measures and imprisonment, the author concludes that the criminal legal theory and practice of our state should be creating a concept of efficient use of "alternative measures". They should replace prison sentence. Also, the author analyzes the most important international documents that recommended a restrictive application of imprisonment on account of wide application of non-institutional treatment.
BETWEEN IMPRISONMENT AND PROBATION: ADVANTAGES AND DISADVANTAGES OF (NON)IMPLEMENTATION OF ALTERNATIVE MEASURES AND PRISON SENTENCE
Keywords: imprisonment, alternative measures, conditional sentence, probation, international documents, recidivism, crime policy, penal policy of courts; казна затвор, алтернативни мерки, условна осуда, пробација, меѓународни документи, рецидивизам, криминална политика, казнена политика на судови